Peningkatan Motorik Halus Anak Usia Dini Melalui Kegiatan Finger Painting Di KB Paud Citra Nusantara - Mahfudoh Tunisa; Amat Hidayat; Ratu Yustika Rini (Getpress Management Journals, 2025)
This research is based on the urgency of the motor development process is very closely related to the motor center in the brain. Motor skills develop in line with muscle and nerve maturation. In this case, it was found that the fine motor skills of children aged 4-5 years were considered lacking based on the results of observations in the activities of scissors, drawing lines and in controlling the coordination of hand and eye movements at KB PAUD Citra Nusantara. This study uses a quantitative method with an approach using  the One Group Pretest-Posttest Design pre-experimental model  in this study, 35 students and students aged 4-5 years from classes A1 and A2. They were observed twice: before (pretest) and after (posttest) doing finger painting activities. This method starts with collecting data, interpreting it and then producing appearances and results. The data collection techniques are observation and documentation. The technique of measuring observation items uses a Likert scale. The data validity technique uses the Correl  formula in Microshoft Excel and uses a significance of 5%. The technical data analysis uses the N-gain Score. The place for this research was carried out at KB PAUD Citra Nusantara, Bojong Village, Ragas Masigit Village, Carenang District, and was carried out in February-March 2023. Based on the results of observation and data processing, it can be concluded that the Improvement of Fine Motor Skills of Children Aged 4-5 Years through Finger Painting Activities at KB PAUD Citra Nusantara shows an increase of 74% with the level of effectiveness quite effective.